Access to credit and heterogeneous effects on agricultural technology adoption: Evidence from large rural surveys in Ethiopia - Mekdim D. Regassa; Mohammed B. Degnet; Mequanint B. Melesse (Canadian Journal of Agricultural Economics/Revue canadienne d'agroeconomie, 2023)
Modern agricultural technologies hold huge potential for increasing productivity and reducing poverty in developing countries. However, adoption levels of these technologies have remained disappointingly low in Africa. This paper analyzes the effect of access to credit on the likelihood of adoption and use intensity of chemical fertilizers using data from large rural surveys in Ethiopia. Using a heteroscedasticity-based identification strategy to address the endogenous nature of access to credit, we find that access to credit has significant positive effects on adoption and intensity of use of chemical fertilizers. However, important heterogeneities are observed. Credit obtained from formal sources is more important for the intensity of use than for the decision to adopt chemical fertilizers. Credit taken with the primary purpose of financing agricultural inputs is more likely to promote adoption of chemical fertilizers than credit taken per se. Furthermore, reported credit effects are larger when estimated against the sample of credit-constrained non-users as compared with the pool of the whole sample of credit non-users. The results remain robust to several sensitivity analyses. Our results yield useful implications for the design, promotion, and targeting of credit services to leverage their effect on adoption of agricultural technologies.
Keywords: 330; chemical fertilizers; credit access; Ethiopia; heterogeneity analysis; heteroscedasticity-based identification; technology adoption